Islamic Accounting: Ethics Concerning the Recording of Debts and Receivables in the Qur'an Surah Al-Baqarah Verse: 282 - Khaulah tranggano; Muthoifin Muthoifin (Prosiding University Research Colloquium, 2022)
The focus of this research is to reveal Islamic accounting ethics: the ethics of accounts payable and the procedures from an Islamic perspective, as well as the implications of the verse al-Baqarah: 282 is applied. This research method uses qualitative and descriptive research methods, the data source used is a literature study, namely by collecting documents sourced from primary data from al-Baqarah: 282, and secondary sources, the approach used is content analysis, and normative. The results of the study concluded that Islamic ethics in terms of accounts payable include: 1). This verse recommends every human being record every transaction activity. 2). these records are used as written evidence that the debt contract has been made, 3). So that in the future no one will be harmed, except for people who carelessly misuse it, 4). This verse is very interesting because it is also referred to as the basis of Islamic accounting arguments. While the implication of this ethics is, rationally it has an impact on both social and state life, has a major impact on economic benefits both individually and socially, adds comfort, tranquility, honesty, and blessings from the concept of recording and being honest in debt-receivable transactions.